DOI: 10.22054/RJQK.2022.68306.2628 ISSN: 2008-9252 eISSN: 2538-2012 Received: 04/06/2022 Accepted: 22/06/20211 Analysis and Critique of Fatemeh Mernisi's View on Original Research Hijab with Emphasis on Verse 53 of Surah Al-Ahzab - Ali Sharifi; Ashkan Naiemi; Fereshte Kuini (پژوهش نامه معارف قرآنی, 2022)
n recent decades, the hijab has been one of the most important rulings in the field of women, which has been considered by currents called religious modernists and Islamic feminism And they have tried to recite the verses of hijab with a customary attitude based on respect for women's rights. One of these people is Fatemeh Mernissi, who in one of her works called "The veil and The Male elites " examines verse 53 of Surah Al-Ahzab and believes that the concept of hijab in the verse in question means a barrier between two men. This research uses analytical-descriptive method and using valid interpretive and religious sources to study and analyze the views and methods of this researcher on the issue of hijab. According to studies, Mernissi's view is due to the limitation and lack of resources and selective use of them, confusion between veiling and covering women, deviation from the appearance of verse 53 of Surah Al-Ahzab and the context of adjacent verses, lack of attention to semantic relativity and lack Paying attention to the verses that explicitly legislate the ruling on hijab for Muslim women is flawed and not based on a solid basis